Popularization of Islamic Ecology in the Pandawara Group Waste Management Movement on Social Media - Rafika Umrah, Vivi Sri (Sahabat Publikasi, 2024)
Waste is a crucial issue that occurs due to the increasing consumerism of people in various circles. Until it causes natural damage that has occurred everywhere. Nature is considered to have no impact on human actions, but when a natural disaster occurs, humans do not realize that it occurs as a result of their actions. So the main focus in this writing is to understand the responsibility of humans as guardians and conservators of the earth. The goal is to explore and identify the applicable steps of the Pandawara movement in spreading Islamic ecological awareness through social media, Instagram and YouTube. With a theological approach applied to the media ecological theory of Richard West and Lynn H, the results of this study show that the content of the pandawara group has a perception that can affect people's feelings, emotions and awareness, so that the concept of ecology in Islam Hablum mina Allah and Hablum minan nas is reflected in the pandawara movement. The results of the study were also analyzed from netizens' responses through the comment column as a reference for the basis of the research